Investigation of Middle School Students’ Attitudes towards Science, Technology, Engineering and Mathematics (STEM) Education and Determination of the Predictors - Cennet Göloğlu Demir; Nagihan Tanik Önal; Nezih Önal (Journal of Science Learning, 2021)
The purpose of the current study is to investigate middle school students’ attitudes towards Science, Technology, Engineering, and Mathematics (STEM) education and to determine the predictors of these attitudes. The study was designed according to the relational survey model, one of the quantitative research designs. The sample of the study is comprised of 408 middle school 6th, 7th, and 8th-grade students. The data of the current study were collected using a STEM-oriented attitude scale. An independent samples t-test, one-way variance analysis, and stepwise multiple regression analysis were used to analyze the collected data. As a result of these analyses, it was determined that the students’ attitudes towards STEM vary significantly depending on the students’ gender, grade level, participation in in-school and out-of-school social activities, science and mathematics achievement. The most effective three predictors of STEM were found to be science achievement, being a 6th grader, and being female. The state of being female was found to be negatively correlated with the prediction of the attitudes towards STEM. As a conclusion of the study, suggestions were made to eliminate gender-based differences in STEM attitudes, increase STEM activities in upper grades, and for career planning.